2020
DOI: 10.3389/fpsyt.2020.00501
|View full text |Cite
|
Sign up to set email alerts
|

Reducing Allostatic Load in Depression and Anxiety Disorders: Physical Activity and Yoga Practice as Add-On Therapies

Abstract: The allostatic load (AL) index constitutes a useful tool to objectively assess the biological aspects of chronic stress in clinical practice. AL index has been positively correlated with cumulative chronic stress (physical and psychosocial stressors) and with a high risk to develop pathological conditions (e.g., metabolic syndrome, cardiovascular pathology, inflammatory disorders) and the so-called stress-related psychiatric disorders, including anxiety and depressive disorders. Chronic stress has negative eff… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
24
0

Year Published

2021
2021
2025
2025

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 32 publications
(24 citation statements)
references
References 127 publications
0
24
0
Order By: Relevance
“…In our study also, we promoted a task-oriented climate with a learning component as such an environment is reported to be more associated with adaptive behaviors, healthy habits, and autonomous motivation to practice sports outside of school [24]. The interventions based on light-to-moderate physical activity, body awareness, and yoga practice may have synergizing benefits, reducing the negative effects of chronic stress [25]. On the contrary, physical exercise programs conducted in an ego-oriented climate could lead to an extrinsic motivation, which is associated with further abandonment of physical activity [24].…”
Section: Group Evolutionmentioning
confidence: 71%
“…In our study also, we promoted a task-oriented climate with a learning component as such an environment is reported to be more associated with adaptive behaviors, healthy habits, and autonomous motivation to practice sports outside of school [24]. The interventions based on light-to-moderate physical activity, body awareness, and yoga practice may have synergizing benefits, reducing the negative effects of chronic stress [25]. On the contrary, physical exercise programs conducted in an ego-oriented climate could lead to an extrinsic motivation, which is associated with further abandonment of physical activity [24].…”
Section: Group Evolutionmentioning
confidence: 71%
“…Yoga practice was found to have a positive effect on depression and anxiety symptoms in depressed pregnant women and was able to improve mood states in admitted psychiatric patients. Beneficial effects of Yoga on depression outcomes have also been reported in patients with major depressive disorder (19). Yoga is a physical activity that can reduce depressive symptoms in women with postpartum depression (20).…”
Section: Contextmentioning
confidence: 98%
“…Numerous studies have shown that Yoga was effective in decreasing depression and anxiety in general population (16)(17)(18). The mechanism of performing regular exercises in Yoga results in long-term sympathetic effects, changes hippocampal function, and prevents depression (19). A meta-analysis of randomized controlled trials showed that Yoga practice may reduce cortisol, autonomic response (changes in heart rate and systolic blood pressure), cytokines, and lipid levels and, as a result, reduce stress symptoms (19).…”
Section: Contextmentioning
confidence: 99%
See 1 more Smart Citation
“…4 Previous research demonstrated that elevated AL predicted adverse health outcomes in later life, 5 including physical and cognitive decline, 6 malignant neoplasms, cardiometabolic and respiratory diseases, 7 depressive symptoms, 8 and all-cause mortality, 9 better than any individual biomarker or the metabolic syndrome. 5 6 Hence, assessment of AL allows early identification of people at increased health risks when the physiological dysregulations are still reversible, such that timely interventions, such as exercise, 10 drug therapy, diet and psychological intervention, 11 can be provided to prevent adverse health outcomes.…”
Section: Strengths and Limitations Of This Studymentioning
confidence: 99%